How design features in digital math games support learning and mathematics connections. (February 2019) - Moyer-Packenham, Patricia S.; Lommatsch, Christina W.; Litster, Kristy; Ashby, Jill; Bullock, Emma K.; Roxburgh, Allison L.; Shumway, Jessica F.; Speed, Emily; Covington, Benjamin; Hartmann, Christine; Clarke-Midura, Jody; Skaria, Joel; et al.
Abstract: Current research shows that digital games can significantly enhance children's learning. The purpose of this study was to examine how design features in 12 digital math games influenced children's learning. The participants in this study were 193 children in Grades 2 through 6 (ages 8–12). During clinical interviews, children in the study completed pre-tests, interacted with digital math games, responded to questions about the digital math games, and completed post-tests. We recorded the interactions using two video perspectives that recorded children's gameplay and responses to interviewers. We employed mixed methods to analyze the data and identify salient patterns in children's experiences with the digital math games. The analysis revealed significant gains for 9 of the 12 digital games and most children were aware of the design features in the games. There were eight prominent categories of design features in the video data that supported learning and mathematics connections. Six categories focused on how the design features supported learning in the digital games. These categories included: accuracy feedback, unlimited/multiple attempts, information tutorials and hints, focused constraint, progressive levels, and game efficiency. Two categories were more specific to embodied cognition and action with the mathematics, and focused on how design features promoted mathematics connections. These categories included: linked representations and linked physical actions. The digital games in this study that did not include linked representations and opportunities for linked physical actions as design features did not produce significant gains. These results suggest the key role of mathematics-specific design features in the design of digital math games. Highlights: Children made significant learning gains when using 9 of the 12 digital math games. Children's awareness of the mathematics in digital math games impacted learning. Eight categories of game design features supported children's learning. Learning gains were tied to design features that linked representations to the mathematics. Learning gains were tied to design features that linked physical actions to the mathematics.